PENGEMBANGAN BANK SOAL PJOK KELAS VI SD BERBASIS APLIKASI ANDROID - Darma Permadi, Gigih; A, Palmizal; Munar, Hendri; Ilham; Nugraha, Ugi; Junresti Daya, Wawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an Android-based Physical Education, Sports, andHealth (PJOK) question bank application for sixth-grade elementary schoolstudents, determine the feasibility of the product based on expert validation, andanalyze its effectiveness in supporting the learning evaluation process. The studyused a Research and Development (R&D) method with the ADDIE developmentmodel, which consists of five stages: analysis, design, development,implementation, and evaluation. The product developed is an Android-basedapplication containing PJOK learning materials, a collection of practice questions,interactive quizzes, and automatic score displays to assist students in practicingindependently. The feasibility of the product was assessed through validation bymaterial experts and media experts. The results showed that the material validationobtained a score of 85% with a “very good” category, while the media validationobtained a score of 90% with a “very good” category. Furthermore, the effectivenesstest related to media display, content, and learning process showed an overall scoreof 90% categorized as “very good”. These results indicate that the Android-basedPJOK question bank application is feasible and effective to be used as a learningevaluation medium that can support teachers in managing assessment instrumentsand help students practice questions more interactively, flexibly, and independently. Keywords: Android application, question bank, PJOK learning evaluation,elementary school.